The abundance, diversity, and assemblage structure of the macrobenthos at the South Georgia shelf methane seeps - Anderson, Madeline P. B. C.; Reid, William D. K.; Bohrmann, Gerhard; Dohrmann, Ingrid; Hollyman, Philip R.; Kasten, Sabine; Pape, Thomas; Römer, Miriam; Newton, Jason; Wigham, Ben D.; Linse, Katrin (Frontiers in Marine Science, 2025)
A quarter of all marine methane, a potent greenhouse gas, is estimated to be hosted in Southern Ocean sediments. Climate change-induced ocean warming and ice shelf melting risk the stability of sedimentary gas hydrates, resulting in potential degassing and establishment of marine methane seeps. While methane seeps can originate from various sources, the destabilisation of gas hydrates may contribute to the formation and persistence of some active seeps. The impact of these seeps and their risks to the diverse sub-Antarctic and Antarctic benthic shelf fauna is uncertain. As a sentinel for change in the sub-Antarctic and wider Antarctic region, this study explores South Georgia’s continental shelf macrobenthic methane seep assemblages, for their diversity, richness, and abundance, and their environmental drivers influencing macrofaunal community composition. Seven of South Georgia’s shelf troughs hosting active methane seeps were investigated during RV METEOR’s M134 expedition in 2017. Species richness at 11 stations ranged from 19–51 species from a total of 103 species discovered across all sites. Station abundance ranged from 3,303–30,326 m². Diversity was higher at stations with greater methane- and sulfate-flux, and hydrogen sulfide at 25 cm depth. Abundance and richness were lower where surface sediment had high hydrogen sulfide concentrations. Abundance and species richness were lower at stations dominated by iron-reduction in the sediment. Assemblages were characterized by the presence of Southern Ocean species and by the absence of megafaunal chemosynthetic taxa. Arthropods, mostly crustacean, and annelid species made up three quarters of overall species richness, while molluscan and echinoderm species were depauperate with only 15 species. Compared with Southern Ocean macrobenthic assemblages, the South Georgia seep assemblages from sediments with gas hydrates present in the near-surface showed a lower species richness and change in taxon composition, also accompanied by lower numbers of calcium-carbonate shell bearing taxa. The current diverse benthic Antarctic biodiversity, especially the diversity of calcifiers, is likely at risk when methane seeps become established on Southern Ocean continental shelves as the reduction in habitat diversity leads to the decline in taxonomic diversity and species richness.